Comparison of the Analgesic Effect of Diclofenac Sodium-Eudragit® RS100 Solid Dispersion and Nanoparticles Using Formalin Test in the Rats - Khosro Adibkia; Alireza Mohajjel Nayebi; Mohammad Barzegar-Jalali; Siavash Hosseinzadeh; Saeed Ghanbarzadeh; Afshin Shiva (Tabriz University of Medical Sciences, 2015)
Purpose: In this study the intensity and duration of analgesic effect of diclofenac Na - Eudragit® RS100 solid dispersion and nanoparticles were evaluated by using formalin test in the rats. Methods: The animals received different formulations of diclofenac Na and subsequently 50 μl of formalin solution (2.5%) was injected subcutaneously in the right paws after 1 h, 2 h and 3 h. The paw licking behavior was then evaluated in two phases. A dose of 20 mg/kg of pure diclofenac Na powder was determined as effective dose. Results: In the first phase, in term of reduced paw licking time, no significant differences were found in any of the groups compared to the control group. However, in the second phase, the animals which received pure drug powder and the physical mixture of diclofenac Na with Eudragit® RS100 showed significant differences at the first and second hours. In the animals received the nanoparticles and solid dispersion, significant differences were observed in the third hour compared to the control group. Conclusion: The analgesic effect of diclofenac Na could be improved by formulating its nanoparticles and solid dispersion with Eudragit® RS100. However, the nanoparticles revealed significantly higher analgesic effect than solid dispersion.